Implementación de un sistema para caracterización de los parámetros de corriente-voltaje y potencia-voltaje en paneles fotovoltaicos - Chasi Toapanta, Luis Jacinto (2022)
The technological proposal aims to implement a system for characterizing the I-V and P-V operation curves by recording measurements of the electrical parameters in the photovoltaic panels to determine the production capacity under normal operating conditions. The study arises from the lack of knowledge of current electrical parameters, voltage of the 3 kW photovoltaic station, limiting the monitoring of the maximum power generated, as well as maintenance actions after the years of useful life used. The methodology used is of an applicative nature with the use of bibliographic, field, inductive and deductive methods. The results show that the group of Simax SP636 panels in a morning schedule with cloudy weather conditions and random solar events, from 9:30 A.M. until 13:30 P.M., they offer an average voltage of 16.84 V and a current of 3.45 A; in addition to an average power of 57.50 W. For its part, the group of Ving Solar Spectrum YL.235P panels, at the same measurement time, revealed an average voltage of 19.13 V and a current of 6.01 A, with a power of 114.68 W on a temperate and cloudy day with solar irradiation during the middle of the day. Among the conclusions, it stands out that the module is capable of supplying a maximum power of 227.8 W, under the effects of a certain irradiation G I kW/m² and a temperature T 25°C, which is very close to the operational work of the panels. photovoltaic.